Performance evaluation of a V-Trough solar concentrator photovoltaic system - Chua Y.L.; Sheng N.Y.R.; Tay T.T.; Koh Y.Y. (American Institute of Physics Inc., 2023)
This paper investigates the performance of employing a 60 V-Trough solar concentrator onto monocrystalline photovoltaic systems operating in a tropical region. An experimental run is conducted by benchmarking the V-Trough solar concentrator photovoltaic system with a similarly rated standalone, basic photovoltaic system. Experimental results obtained confirmed that a V-Trough solar concentrator improves the efficiency of a monocrystalline photovoltaic cell in a tropical region. 2018 Author(s).